Biomechanics feedback for rowing - Smith, R. M.; Loschner, C. (Journal of Sports Sciences, 2002)
Factors that affect boat speed are important determinants of rowing performance and should form the basis of feedback to rowers and their coaches. Biomechanical analysis of rowing has led to variables that are causally linked to boat speed. With modern technology, these variables can be measured and feedback can be presented instantaneously on-water, or be presented simultaneously with video after the event. This paper demonstrates the links between the criterion of success in rowing, the time for completing 2000 m and the forces acting on the boat, and describes an instrumentation system for providing feedback of these variables to rowers and coaches. These feedback techniques have been used with rowers from national to Olympic competition standard. Aspects of technique have been linked to the determinants of boat speed and several examples are presented here. The motor learning literature supports the effectiveness of kinetic information feedback for the improvement of motor skill and provides a relevant conceptual framework for the improvement of rowing performance. However, although rowers and their coaches value this feedback, further research must be undertaken to establish a sound basis for comparing the effectiveness of such feedback compared with traditional styles, such as verbal feedback of performance.